Faktor-Faktor yang Mempengaruhi Keputusan dalam Memilih Universitas Negeri di Indonesia: Studi pada Siswa-Siswi SMA Kelas XII Sumatera Utara - Wike Vivi; Rulianda P. Wibowo; Fadli (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The objective of the research is to find out the main priority which highly influenced students to continue their study to the universities, especially public universities in Indonesia. Various facilities and services provided by the universities become the consideration in choosing the universities according their talent, interest, and selection. These alternatives are presented in 5 (five) criteria and sub-criteria which will be analyzed, and which factor that will become their main priority in choosing the universities according to their willingness and expectation. The research uses AHP method by calculating the weight of priority based on the response to the questionnaires in 111 Grade XII Senior Hight School students as the respondents from high ranking (A) schools in North Sumatera. The result of the research shows that of the five criteria, the criterion of University Image has the highest position with the weight of 0.33. In the highest priority of sub-criterion of University Image is International Accreditation with the weight of 0.24, and in sub-criterion of Tuition is cost of living, in sub-criterion of Tuition is cost of living, in sub-criterion of Location is the university which is located in urban area with the weight of 0.13, the sub-criterion of Facility and Infrastructure provided by the university is IT facility for Learning Media with the weight of 0.16. Therefore, based on the main priority of the criteria and each criterion which have been obtained, it is expected that the management of the public universities in Indonesia know what has to be heeded and improved in the interest of the prospective students.